2010
DOI: 10.1302/0301-620x.92b1.22609
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between surgery and physiotherapy in the treatment of small and medium-sized tears of the rotator cuff

Abstract: In order to compare the outcome from surgical repair and physiotherapy, 103 patients with symptomatic small and medium-sized tears of the rotator cuff were randomly allocated to one of the two approaches. The primary outcome measure was the Constant score, and secondary outcome measures included the self-report section of the American Shoulder and Elbow Surgeons score, the Short Form 36 Health Survey and subscores for shoulder movement, pain, strength and patient satisfaction. Scores were taken at baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
112
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 53 publications
(54 reference statements)
5
112
0
4
Order By: Relevance
“…The number of patients suffering significant complications was very low and less than the rate described by Moosmayer et al, 60 but similar to that described by Kukkonen et al 59 The infection rate in this study was 0.7% and the rate of revision surgery was 1.5%.…”
Section: Complicationssupporting
confidence: 87%
See 1 more Smart Citation
“…The number of patients suffering significant complications was very low and less than the rate described by Moosmayer et al, 60 but similar to that described by Kukkonen et al 59 The infection rate in this study was 0.7% and the rate of revision surgery was 1.5%.…”
Section: Complicationssupporting
confidence: 87%
“…53 We found two further trials of surgery compared with conservative care published since the trial began. In the single-centre trial of small and medium tears by Moosmayer et al, 60 the surgical group had better outcomes at 1 year. This study reported a full-thickness re-tear rate of 8% and a partial-thickness re-tear rate of 12%.…”
Section: Comparison With Other Randomised Clinical Trialsmentioning
confidence: 91%
“…The authors concluded that both approaches can be considered for the treatment of patients with small and medium-sized rotator cuff tears, but better results can be expected after primary surgical repair [14].…”
Section: Scenariomentioning
confidence: 99%
“…Scientific evidence is limited, because only 2 randomized controlled trials have compared the 2 modalities, and they present conflicting results. 17,24,25 A study by Kukkonen et al 17 found no difference between the treatments, and in a study by Moosmayer et al, 24 surgical repair was favorable.…”
mentioning
confidence: 96%
“…Surgical repair and conservative treatment are both described, and acceptable results are reported for both. 2,6,11,17,24 Those who favor surgical repair worry that tear progression over time will lead to increased disability with conservative treatment of full-thickness tears. The rotator cuff has limited capabilities for healing without repair, 33 yet conservative treatment often yields an acceptable outcome.…”
mentioning
confidence: 99%